The Effects of Task Complexity on the Complexity of the Second Language Written Production - Umi Kalsom, Masrom; Nik Aloesnita, Nik Mohd Alwi; Nor Shidrah, Mat Daud (University of Central Lancashire, 2015)
This paper investigates the effects of manipulating task complexity on the complexity of learner language production during asynchronous computer-mediated communication (ACMC) writing tasks. This study draws the construct of cognitive complexity indicated in Robinson’s Cognition Hypothesis (Robinson 2001a, 2003a, 2003b, 2005, 2007a, 2007b) which predicts that complex tasks made along resource-directing dimension will lead to greater complexity of language production while complex tasks made along resource-dispersing dimension will result in less complex language production. However, research on the effects of manipulating task complexity along both resource-directing and resource-dispersing dimensions is so far inconclusive.